The Role of Jordanian Legislation in Countering Cybercrime and its Impact on Library Information Security - ALkawakzeh, Ashraf Ali Oqlah (Dirasat: Shari'a and Law Sciences, 2020)
The aim of this study was to identify the impact of electronic crimes on the information security in libraries, and to determine the adequacy of national legislation to confront and combat electronic crimes that threaten the information security in libraries and constitute a violation of it.the researcher used the analytical approach by analyzing the legal texts in the legislation and indicating the adequacy of their shortcomings, and the comparative descriptive approach through the legal description of electronic crimes and their impact on the information security of libraries in Jordanian legislation. The study reached a set of conclusions and recommendations, the most important of which was that information and data in libraries are threatened by risks generated by the technological revolution, and they need technical and legal means of protection at the same time to face their risks, and the need remains urgent to develop special texts for the law of electronic crimes that deal with this type of crime in detail and commensurate with the enormous development in the field of technological means, due to the lack of provisions of the law of electronic crimes related to the protection of information security of libraries in particular. The study recommended the need for international cooperation in combating cybercrime by holding conferences, exchanging experiences and concluding agreements.